Evaluasi Pelaksanaan Learning Management System (LMS) Di Sekolah Penggerak SMPK 1 Harapan Denpasar - I.M.Y. Wirawan; I.M. Yudana; I.N. Natajaya (Pascasarjana Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effectiveness of the components of context, input, process, product and the constraints that occur in the implementation of the Learning Management System (LMS) at the Driving School of SMPK 1 Harapan Denpasar. This research is a program evaluation research with the CIPP model. The population in this study amounted to 435 people, while the sample amounted to 70 people. Data context, input, process, product in this study were collected by using a questionnaire using a Likert scale model. The data analysis method used in this study is a quantitative descriptive analysis method. To determine the effectiveness of implementing the Learning Management System (LMS) the raw scores were transformed into Z-scores and then into T-Scores and then verified into the Glickman Quadrant prototype. Based on the results of the research data analysis that has been carried out, the results show that: 1) The effectiveness of the implementation of the Learning Management System (LMS) system in terms of the context shows effective results, 2) in terms of input, effective results are obtained, 3) in terms of the process, effective results are obtained, 4 ) and in terms of the product, the results obtained are effective, 5) The results of a joint evaluation of the implementation of the Learning Management System (LMS) in terms of context, input, process, product are very effective, and 6) The constraints faced in implementing the system Learning Management System (LMS) are 1) some students from elementary schools who have not implemented IT, 2) some education staff are still not ready to use applications that are constantly being updated, 3) some students are not ready because some have not used smartphones. or quota problems.